Diseño y construcción de un banco didáctico electromecánico (2016)
This degree project is the design and construction of an Electromechanical Didactic Bank, which allows doing theoretical and practical classes in different subjects of career Electromechanical Engineering and Technology. The machine has different devices, including an Variable Speed Drive, which controls an electric motor, as it can be configured in many ways, this being one of the main components of the machine. Furthermore, it has an electromagnetic clutch, made from a compressor of an air conditioner of a car. It also has a manual gearbox five-speed, which has cutouts in its hou